Korelasi asupan makronutrien dengan indeks massa tubuh, kadar gula darah, dan protein total darah pada pengguna narkoba - Ginta Siahaan; Tiarlince Bakara; Yusnita Yusnita; Kasmiyeti Kasmiyeti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Correlation of macronutrient intake with body mass index, blood sugar levels, and total blood protein in drug usersBackground: Random blood sugar level and total blood protein need to be measured among drug users because their macronutrient intakes (carbohydrates, fat, protein, and energy) are not appropriate to the pattern of daily habits before uses drugs. Drug users had decreased appetite during the influence and withdrawal symptoms of drugs with the impacts on their body mass index (BMI). Objective: To analyze the correlation of macronutrient intakes between the random blood sugar level, total blood protein, and BMI drug users.Methods: This research was conducted with a cross-sectional design and observational study. 73 drug users were included in the study with the screening by inclusion criteria. 24-hour food recall was used to collect the macronutrient intakes, random blood sugar levels and total blood protein were monitored by the GOD-PAP method, and BMI was measured by weight and height. Data analysis used Pearson’s correlation test in bivariate and multivariate was carried out by multiple linear regressions. Results: Pearson’s correlation analysis showed that there was a significant correlation between macronutrient intakes (energy, carbohydrate, fat) with random blood sugar level, total blood protein, and BMI. BMI was the most affected by energy (β=0.531), random blood sugar level was the most affected by carbohydrates (β=0.073), and total blood protein was the most affected by protein (β=0.837).Conclusions: Macronutrient intake is significantly related to BMI, random blood sugar levels, and total blood protein in drug users. Community collaboration with related parties such as the public health service and National Narcotics Agency will very quickly detect drug side effects early on eating disorders that will affect the nutritional status of its users.